2000
DOI: 10.1002/1521-396x(200003)178:1<331::aid-pssa331>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality of Excitons in InGaN-Based Light Emitting Devices

Abstract: Temperature dependence of radiative and non-radiative recombination times has been investigated in In x Ga 1± ±x N-based light emitting devices by employing time-resolved luminescence spectroscopy. The mean In-composition (x value) assessed in this study is 10%, 20% and 30% whose emissions at 300 K correspond to near ultraviolet (390 nm), violet (422 nm) and blue (471 nm), respectively. It was found that the degree of exciton localization was enhanced with increasing In-composition in In x Ga 1± ±x N active la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 16 publications
0
40
0
1
Order By: Relevance
“…The use of less than 1-nm-thick In-rich InGaN QW layer as an active layer can be a candidate for near-UV source, which might replace the conventional low-indium content ͑Ͻ10% ͒, thicker InGaN QW layer. [13][14][15] In conclusion, In-rich InGaN / GaN MQWs were grown by MOCVD. It was found that the control of interfacial quality by means of GI is a very important factor in improving structural properties of MQWs.…”
Section: Room Temperature Near-ultraviolet Emission From In-rich Ingamentioning
confidence: 99%
“…The use of less than 1-nm-thick In-rich InGaN QW layer as an active layer can be a candidate for near-UV source, which might replace the conventional low-indium content ͑Ͻ10% ͒, thicker InGaN QW layer. [13][14][15] In conclusion, In-rich InGaN / GaN MQWs were grown by MOCVD. It was found that the control of interfacial quality by means of GI is a very important factor in improving structural properties of MQWs.…”
Section: Room Temperature Near-ultraviolet Emission From In-rich Ingamentioning
confidence: 99%
“…One is to increase the internal quantum efficiency; the other is to increase the light extraction efficiency. The internal quantum efficiency is determined by crystal quality and epitaxial layer structure, and it is reported that the high internal quantum efficiency for blue GaN-LED has already reached 70% [3] . However, the external quantum efficiency is still in low level, which results from the limitations of the large difference in the refractive index between the semiconductor and the air.…”
Section: Introductionmentioning
confidence: 96%
“…Two main approaches are used to improve the external quantum efficiency: increasing the internal quantum efficiency and/or enlarging the light extraction efficiency. Very high values (approaching 100%) of internal quantum efficiency have already been demonstrated [3][4][5]. Thus, further improvements of the IQE may not be readily achieved.…”
Section: Introductionmentioning
confidence: 99%